Coach’s Role In Overcoming The Void Period For Young Footballers - Abdelkrim, Senouci; Habib, enchenni (Journal of Sport Science Technology and Physical Activities, 2024)
The study aims to identify the role of the coach in helping the players and the team to overcome the void stage during the competition, which is the stage in which the level of performance declines, whether individual or collective performance, as we assumed that the coach's experience and his focus on the psychological aspect, has a positive role in the team's overcoming of the void stage. For this purpose, we used the descriptive survey method, on a sample of 50 coaches, chosen randomly. To collect data, we used a questionnaire designed by the two researchers, consisting of three axes and 20 questions. After collecting the results and processing them statistically, we concluded that the junior team, during its passage through a void, the trainer directs his attention and focus on the educational, skillful side in the first, and the psychological side in the second, relying on this as the reason for his field experience in employing the psychological aspect. On this basis, the study recommended the necessity of training the trainers from the psychological side, in addition to making sure to prepare a unified training program for the junior class, in order to facilitate the process of their inclusion in the senior class.